Unlocking Quasi‐Monophase Behavior in NASICON Cathode to Drive Fast‐Charging Toward Durable Sodium‐Ion Batteries - Zhao, Xin‐Xin; Wang, Xiao‐Tong; Gu, Zhen‐Yi; Guo, Jin‐Zhi; Cao, Jun‐Ming; Liu, Yan; Li, Jie; Huang, Zhi‐Xiong; Zhang, Jing‐Ping; Wu, Xing‐Long (Advanced functional materials, 2024)
The NASICON cathode, Na3V2(PO4)3, has garnered significant attention due to its robust framework with fast Na+ migration. To expand its application scenarios by diversified electronic reaction, the substitution of vanadium with cost‐effective and abundant redox elements is a special research topic. Nevertheless, in terms of reducing toxicity, increasing Na content and widening voltage range, the V4+/5+ redox couple in Na4FeV(PO4)3 often accompanies asymmetric and irreversible electrochemical reactions that pose a dilemma for capacity and structural stability, especially at high currents. Herein, in this work, Na4FeV1/3Ti2/3(PO4)3 (NFVT) has achieved highly reactive of multiple electron transfer (Ti2+/3+, Fe2+/3+, and V3+/4+/5+) by utilizing the redox reaction with quasi‐monophase behavior, and it can reserve great capacity retention after 3,000 cycles. More competitively, its boosting kinetics makes the fast‐charging characteristic, just requiring only 3.63 min to reach 80% state of charge at 2 C. The rapid ion/electron transport dynamics can achieve the decay of only 0.043% per cycle by unlocking the quasi‐monophase behavior in the framework of NFVT full cells. The present study provides a fresh perspective on designing cathode materials with fast‐charging capabilities for sodium‐ion batteries. A particular phase tune changes the two‐phase reaction to quasi‐monophase reaction, making Na4FeV1/3Ti2/3(PO4)3 (NFVT) obtain multi‐electron transfer with low strain during electrochemical process. Hence NFVT half cells render the balancing the specific capacity, cycle durability, and the exceptional fast‐charging capabilities, as well as low‐capacity decay in full cells, thereby elevating the competitiveness for multi‐electron transfer in high‐performance sodium‐ion batteries.